STRATEGI KOMUNIKASI PEMASARAN MELALUI MEDIA SOSIAL INSTAGRAM DALAM MEMPROMOSIKAN PRODUK STUDI PADA HANAKA CLASSIC DI DENPASAR - PUTRI, NI KOMANG AYU RATIH ANGGA; WINAYA, NI NYOMAN TERISTIYANI; RIYASA, IDA AYU PUTRI WIDIASUARI (Ganec Swara, 2025)
This research analyzes the marketing communication strategies employed by Hanaka Classic, an MSME in the fashion sector in Bali, through the social media platform Instagram to promote their products. Considering the importance of the fashion industry in tourism and consumer needs in Bali, this study aims to understand how these strategies can boost sales. The research methods used include observation, interviews, and documentation, as well as a SWOT analysis to identify the company's strengths, weaknesses, opportunities, and threats. The research findings indicate that Hanaka Classic is in a favorable position (Quadrant I) with the potential for rapid growth. The recommended strategies include increasing investment in digital marketing, developing new products, expanding market reach, and forming partnerships with influencers. The Internal-External (IE) Matrix suggests focusing on vertical growth strategies by enhancing control over distribution and suppliers. Additionally, the study provides theoretical contributions to understanding social media marketing and offers practical insights for MSMEs in formulating effective marketing strategies. Practical recommendations include developing social media, maintaining consistency in content uploads, and selecting the right influencers to enhance product appeal.